The effect of chemical structure of carboxylate molecules on hydroxyapatite nanoparticles. A structural and morphological study - Lorenzo Degli Esposti; Alessio Adamiano; Dritan Siliqi; Cinzia Giannini; Michele Iafisco (Bioactive Materials, 2021)
Being the most abundant non-macromolecular organic component of bone, the role of citrate (Cit) in hydroxyapatite (HA) crystallization is of high relevance. In this work we have investigated the influence of hydroxycitrate (CitOH) and glutarate (Glr) on HA crystallization in terms of particle growth, composition, and morphology in comparison to Cit. CitOH and Glr have been selected for this work because they share the same backbone structure of Cit but bear different functional groups in the central region. Our data has revealed that CitOH strongly inhibits HA crystallization more efficiently than Cit. CitOH-HA nanoparticles are composed of platy, elongated particles similar to those of Cit-HA but they are ca. twice smaller and have a lower crystal order. On the other hand, Glr does not inhibit HA crystallization as Cit, but leads to the formation of OCP platelets that convert with maturation time to HA nanorods with larger aspect ratio than Cit-HA. In comparison to Cit-HA samples, Glr-HA nanoparticles have bigger dimensions, and higher structural order. Overall, our data reveal that the central carboxyl group of Cit is involved in the selective binding with HA crystal surface and in regulating HA crystal growth. The results of this work highlight new possibilities to control the formation of HA for designing advanced bioactive materials and give new insights on the role of the structure of Cit in regulating the HA morphology.